The New Minerals Legislation in New Zealand (4d1d8bc9-6dc2-4de3-ae08-c537526bc6dc) - Dip L. B (The Australasian Institute of Mining and Metallurgy, 1990)
This paper describes the new legislative regime that will apply to the regulation of the minerals industry in New Zealand.The reform of New Zealand's minerals legislation was initiated in January 1988 when the Minister for the Environment, Rt Hon Geoffrey Palmer, announced the Government's intention to review all the major laws governing New Zealand's resources. The Resource Management Bill is scheduled for introduction to the House in December 1989 and its date of enactment is scheduled for June 1990.